Analysis of Factors That Influence The Need for E-Commerce Audit Services - Putri Nurmala; Nanda Sofia Oktaviani; Akhmad Sigit Adiwibowo (EAJ (Economic and Accounting Journal), 2022)
This study aims to determine how the influence of E-Commerce-business Development, Accounting Information Technology Systems and Auditor Skills on the Need for E-Commerce Audit Services at Public Accounting Firms in South Jakarta, both partially and simultaneously. This study uses a population of all external auditors working at the Public Accounting Firm in South Jakarta. Sampling uses simple random sampling technique, so that the samples used in this study were 59 external auditors from 6 public accounting firms in South Jakarta. The data used are primary data in the form of questionnaires which are distributed directly to respondents. Data analysis methods used in this study are multiple linear regression analysis, descriptive statistical tests and the classic assumption test. The partial test results show that the development of e-commerce-business does not positively influence the need for e-commerce audit services while the accounting information technology system and auditor expertise positively influence the need for e-commerce audit services. Meanwhile, simultaneous test results showed that the-business development of e-commerce, accounting and information technology systems auditor expertise together - the same effect on the need for audit services e-commerce.